Long-acting, wash-resistant antibacterial and deodorant textile product and its manufacturing method

JP2025506476AActive Publication Date: 2025-03-11TH TEXTILE GRAFTING (SZ) CO LTD
View PDF 14 Cites 0 Cited by

Patent Information

Application Number
JP2024547333
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2024-03-22
Publication Date
2025-03-11
Estimated Expiration
2044-03-22

AI Technical Summary

Benefits of technology

【0028】 本発明にかかる長時間作用性の洗濯に強い抗菌消臭繊維製品の製造方法は、電子ビームによりグラフト重合反応を引き起こす方式ににより、第4級アンモニウム塩単量体と光触媒粒子とを繊維製品に共有結合させる方式であり、その操作プロセスは、常温で実行でき、現在の繊維製品の後加工プロセスラインに接続できる。現在の工業における従来の抗菌消臭繊維製品の製造方法と比較して、本発明によって製造された抗菌消臭繊維製品は、抗菌消臭基が繊維製品にしっかりと結合し、使用中に脱落しにくく、抗菌消臭機能が長く持続し、人体および環境に安全である。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025506476000001
    Figure 2025506476000001
  • Figure 2025506476000002
    Figure 2025506476000002
  • Figure 2025506476000003
    Figure 2025506476000003
Patent Text Reader

Abstract

The present invention relates to a method for producing a long-acting, wash-resistant antibacterial and deodorizing textile product, which includes reacting inorganic photocatalyst particles with a carbon-carbon double bond-containing silane coupling agent to modify the photocatalyst surface with carbon-carbon double bonds, and then inducing graft polymerization by irradiation with an electron beam to generate active free radicals in the textile product, thereby inducing graft polymerization of a carbon-carbon double bond functional group-containing quaternary ammonium salt monomer and the photocatalyst particles modified with a carbon-carbon double bond functional group, thereby firmly fixing the polyquaternary ammonium salt and the photocatalyst particles to the textile product through a covalent bond, thereby imparting antibacterial and deodorizing functions to the textile product. The present invention also relates to a textile product obtained by the above-mentioned production method. The present invention relates to a method for inducing a graft polymerization reaction by an electron beam to bond a quaternary ammonium salt monomer and photocatalyst particles to the textile product through a covalent bond, which is carried out at room temperature, and the antibacterial and deodorizing groups of the produced textile product are firmly bonded to the textile product, are not easily dropped off during use, and have a long-lasting antibacterial and deodorizing function, which is safe for the human body and the environment.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a textile product, and more particularly to a long-acting, launderable, antibacterial and deodorant textile product and a method for producing the same. [Background technology]

[0002] Textile products are indispensable to human life. With the development of the economy and the improvement of people's living standards, people's demands for textile products go beyond covering the body, keeping warm and maintaining beauty; they also expect more functions from textile products, such as waterproof, breathable, UV protection, antibacterial and deodorizing properties.

[0003] Antibacterial and deodorant textile products are a kind of functional textile products that improve people's quality of life. Its antibacterial function has the effect of killing and inhibiting the growth of various bacteria and other microorganisms in textile products, preventing harmful bacteria and other microorganisms from breeding and multiplying and penetrating the human body through contact, which helps protect the health of users. At the same time, antibacterial functional textile products can inhibit the decomposition of human secretions by microorganisms, thereby preventing the production of odorous small molecular substances. Deodorant functional textile products can not only deodorize odorous small molecular substances produced by microorganisms, but also remove odorous small molecular substances emitted from the body through adsorption or decomposition, which can increase the comfort of oneself and those around.

[0004] After years of development, textile products with antibacterial function have some mature processes and considerable market size. Antibacterial agents commonly used in textile products can be divided into two categories: inorganic and organic. Inorganic antibacterial agents include nano metal particles (such as nano silver, nano gold, etc., of which nano silver is prohibited in some countries due to its toxicity to the human body), nano inorganic substances (such as nano zinc oxide, etc.), metal salts (copper salts such as copper sulfate, silver salts), and organic antibacterial agents (chitosan, guanidine-based antibacterial agents, quaternary ammonium salt-based antibacterial agents, etc.). The method of manufacturing antibacterial textile products commonly used in industry is to use a post-processing method in which the antibacterial agent dispersion solution is high-temperature padded to attach the antibacterial agent to the surface of the textile product, and in some cases, a small amount of adhesive is added to the dispersion solution to increase the adhesion to attach the antibacterial agent to the textile product.

[0005] Some of the causes of odors emanating from the human body are odors such as ammonia gas, isovaleric acid, and acetic acid released during the process of bacteria multiplying on the surface of the skin in a hot and humid environment (e.g., after exercise). As bacteria multiply in large quantities, odors are more likely to be generated. Antibacterial textile products can kill bacteria on the surface of the skin or inhibit bacterial proliferation on the surface of the skin, so they can eliminate such odors. Another part of odors such as old-age odor is mainly derived from nonenal produced by the body's own metabolism. Diabetic patients with diabetic ketoacidosis, advanced kidney disease, and liver dysfunction may also produce odors. In addition to odors emanating from the human body, odors from smoking, cooking in hot pot, etc. can also adhere to clothing, causing discomfort to people around them. Ordinary antibacterial functional textile products cannot deodorize such odors, and in order to deodorize them, a functional substance with the corresponding adsorption or decomposition function must be added separately.

[0006] Photocatalytic materials are a general term for semiconductor materials that have photocatalytic properties. The earliest photocatalytic material discovered was nano-TiO 2It is excited by ultraviolet light irradiation and exerts strong oxidizing properties, killing bacteria and decomposing organic matter such as formaldehyde, so it is expected to be applied in the field of antibacterial deodorization. With the development of technology, more photocatalytic materials with photocatalytic oxidation functions have been synthesized, and the excitation light source is no longer limited to ultraviolet light, and the photocatalytic effect can be exerted even with visible light irradiation.

[0007] Due to the sterilization and photocatalytic decomposition of small molecular organic matter by photocatalytic materials, more and more research has been conducted on the application of photocatalytic materials in antibacterial and deodorant textile products. At present, the main method of using photocatalysts to manufacture antibacterial and deodorant textile products is a post-processing method in which inorganic photocatalytic particles are attached to the surface of textile products with adhesives. The disadvantages of this method are that most of the surface of the photocatalytic particles is covered by the adhesive and cannot function, resulting in waste, the bonding fastness between the inorganic photocatalytic particles and the textile product is not high, and the photocatalytic particles are easily shed due to friction and washing, so that the antibacterial and deodorant function does not last long, and the shed photocatalytic particles may penetrate the environment or the human body and have adverse effects. Another disadvantage of antibacterial and deodorant using photocatalysts is that the time required for the photocatalytic reaction is longer, and the antibacterial and deodorant effect does not appear immediately.

[0008] Quaternary ammonium salts are a general term for positively charged organic substances containing tetravalent nitrogen atoms. Quaternary ammonium salts are often used as antimicrobial preparations such as bactericides, and have been used for a long time and extensively in the fields of water purification, antibacterial fabrics, etc. The positive charge of quaternary ammonium salts can attract the negative charge of the microbial cell membrane or envelope lipid layer of bacteria, etc., thereby capturing microorganisms such as bacteria, and destroying the cell membrane or envelope using the lipophilic alkyl chain, thereby realizing the action of killing the microorganisms. The bactericidal principle of quaternary ammonium salts is a physical effect due to the attraction of charges and the destruction of the lipophilic membrane, so it is safe and effective with few side effects. In particular, polymerized quaternary ammonium salts are often used as disinfectants because they are highly stable, heat-resistant, and difficult to decompose. At the same time, quaternary ammonium salt disinfectants also have a certain deodorizing effect, which can inhibit bacterial proliferation, and thus eradicate the odor caused by bacterial proliferation from the root; at the same time, quaternary ammonium salts can also adsorb small molecule substances with acidic odors, such as acetic acid and isovaleric acid, through charge interaction, and can also adsorb ammonia gas to a certain extent by combining with the lone electron pairs in ammonia gas molecules. When quaternary ammonium salts are combined with textile products, they can achieve good broad-spectrum antibacterial effects and can deodorize some odor sources. In particular, by means of graft copolymerization and the like, quaternary ammonium salts can be strongly and firmly combined with textile products through covalent bonds, making the quaternary ammonium salts less likely to fall off, and the broad-spectrum antibacterial and partial deodorizing functions can be sustained for a longer period of time.

[0009] In summary, quaternary ammonium salts and photocatalysts each have their own advantages and disadvantages in terms of antibacterial and deodorizing properties. Quaternary ammonium salts achieve long-term, wide-range antibacterial and certain deodorizing functions, but their deodorizing functions are limited to certain sources of odor. Photocatalysts have a wide-range deodorizing effect, but with conventional technology it is difficult to firmly bind the photocatalyst to textile products and maintain the results for a long time, and it takes a longer time for the photocatalyst to exert its antibacterial and deodorizing effects. Summary of the Invention [Problem to be solved by the invention]

[0010] In order to solve the problem of the antibacterial and deodorizing function of the antibacterial and deodorizing textile products in the prior art not lasting long, the present invention provides a long-acting, wash-resistant antibacterial and deodorizing textile product and a method for producing the same. [Means for solving the problem]

[0011] The manufacturing method of the long-acting, wash-resistant antibacterial and deodorizing textile product of the present invention includes providing a textile product, inorganic photocatalyst particles, a carbon-carbon double bond-containing silane coupling agent, and a carbon-carbon double bond functional group-containing quaternary ammonium salt monomer; reacting the inorganic photocatalyst particles with the carbon-carbon double bond-containing silane coupling agent to modify the photocatalyst surface with carbon-carbon double bonds; inducing graft polymerization by irradiating with an electron beam; and generating active free radicals in the textile product, thereby inducing graft polymerization of the carbon-carbon double bond functional group-containing quaternary ammonium salt monomer and the photocatalyst particles modified with carbon-carbon double bond functional groups, thereby firmly fixing the polyquaternary ammonium salt and the photocatalyst particles to the textile product through covalent bonds, thereby imparting antibacterial and deodorizing functions to the textile product.

[0012] The basic principle of the present invention is different from the conventional post-processing process of physically adsorbing or adhering functional groups to textile products to produce functional textile products through post-processing, and instead, the active free radicals produced on the textile product by electron beam irradiation cause a free radical addition polymerization reaction of the carbon-carbon double bond functional group, thereby bonding the carbon-carbon double bond functional group-containing antibacterial and deodorant group to the textile product through a covalent bond. Because the covalent bond is very strong, the antibacterial and deodorant functional group is not easily removed from the textile product, and the antibacterial and deodorant function lasts for a long time. Conventional photocatalyst materials are inorganic particles, and the surface does not contain carbon-carbon double bonds, so they cannot participate in the graft polymerization reaction. Therefore, the present invention first treats the surface of the photocatalyst particles with a carbon-carbon double bond-containing silane coupling agent, modifies the carbon-carbon double bonds on the surface, and then grafts them together with a carbon-carbon double bond-containing quaternary ammonium salt antibacterial agent to the textile product, thereby producing an antibacterial and deodorant textile product with long-lasting function.

[0013] In particular, the energy of the electron beam is 5 to 6 orders of magnitude larger than the bond energy of covalent bonds such as carbon-carbon bonds and carbon-hydrogen bonds, so that the electron beam can generate active polymer free radicals on the surface of almost all types of organic polymer materials (so that the present invention is applicable to all types of textiles), and then the active polymer free radicals can be used to cause addition polymerization of the carbon-carbon double bond-containing monomers, so that the antibacterial and deodorant groups can be firmly bonded to the fiber polymers by covalent bonds. This electron beam processing process can be operated at room temperature, and the energy conversion efficiency is much higher than that of the reaction caused by heating. At the same time, since the photocatalyst particles are modified with a silane coupling agent, each particle contains multiple carbon-carbon double bonds, and the modified photocatalyst particles themselves are multifunctional monomers, which can participate in graft polymerization with a higher probability. Therefore, the reaction efficiency of the electron beam grafting method of the present invention is extremely high, and can be increased to 100%, and there is almost no waste discharge, making it environmentally friendly.

[0014] Preferably, the method for producing the long-acting, wash-resistant antibacterial and deodorant textile product includes dispersing the carbon-carbon double bond-containing quaternary ammonium salt monomer and the carbon-carbon double bond-containing photocatalyst particles in an aqueous phase, oil phase, or emulsion, immersing the textile product in the dispersion, pressing and rolling it, irradiating it with an electron accelerator in a nitrogen gas or vacuum atmosphere, washing, and drying it to obtain the long-acting, wash-resistant antibacterial and deodorant textile product. In a preferred embodiment, the mass concentration of the carbon-carbon double bond-containing quaternary ammonium salt monomer in the dispersion is 0.5% to 50%, and the mass concentration of the carbon-carbon double bond-containing photocatalyst particles is between 0.01% and 10%.

[0015] Preferably, the inorganic photocatalytic particles are TiO 2 , ZnO, WO 3 , Fe 2 O 3 , SnO 2 , SrTiO 3 , SiO 2 In a preferred embodiment, the inorganic photocatalytic particles are at least one of the group consisting of TiO 2 , ZnO, Fe 2 O 3 , SnO 2 It is a mixture of one or more of the above.

[0016] Preferably, the carbon-carbon double bond-containing silane coupling agent is at least one of the group consisting of vinyltrichlorosilane, vinyltrimethoxysilane, vinyltriethoxysilane, vinyltris(β-methoxyethoxy)silane, vinyltri-t-butoxysilane, vinyltri-t-butylperoxysilane, vinyltriacetoxysilane, acryloyloxyethyltrimethoxysilane, acryloyloxypropyltrimethoxysilane, methacryloyloxyethyltrimethoxysilane, and methacryloyloxypropyltrimethoxysilane. In a preferred embodiment, the carbon-carbon double bond-containing silane coupling agent is one or a mixture of two or more of vinyltrichlorosilane, vinyltrimethoxysilane, acryloyloxyethyltrimethoxysilane, and methacryloyloxyethyltrimethoxysilane.

[0017] Preferably, the reaction between the inorganic photocatalyst particles and the carbon-carbon double bond-containing silane coupling agent is a reaction in which the inorganic photocatalyst particles are immersed in a water or ethanol solution of the carbon-carbon double bond-containing silane coupling agent to obtain photocatalyst particles modified with carbon-carbon double bonds.

[0018] Preferably, the concentration of the carbon-carbon double bond-containing silane coupling agent in water or ethanol solution is 0.1% to 50%.

[0019] Preferably, the reaction temperature in the reaction in which the inorganic photocatalyst particles are immersed in a water or ethanol solution of a carbon-carbon double bond-containing silane coupling agent is −10° C. to 50° C., and the reaction time is 5 minutes to 72 hours.

[0020] Preferably, the carbon-carbon double bond functional group-containing quaternary ammonium salt monomer is at least one of the group consisting of acryloyloxyethyl trimethyl ammonium chloride, acryloyloxyethyl trimethyl ammonium bromide, methacryloyloxyethyl trimethyl ammonium chloride, methacryloyloxyethyl trimethyl ammonium bromide, dimethyl diallyl ammonium chloride, dimethyl diallyl ammonium bromide, (3-acrylamidopropyl) trimethyl ammonium chloride, (3-acrylamidopropyl) trimethyl ammonium bromide. In a preferred embodiment, the carbon-carbon double bond-containing quaternary ammonium salt monomer is one or a mixture of two or more of acryloyloxyethyl trimethyl ammonium chloride, acryloyloxyethyl trimethyl ammonium bromide, methacryloyloxyethyl trimethyl ammonium chloride, methacryloyloxyethyl trimethyl ammonium bromide, and dimethyl diallyl ammonium chloride.

[0021] Preferably, the electron beam of the electron accelerator is used to irradiate the textile product, the photocatalyst particles modified with carbon-carbon double bonds, and the quaternary ammonium salt monomer containing carbon-carbon double bond functional groups to cause graft polymerization. The present invention introduces the advantages of graft polymerization by electron accelerator radiation on the surface of polymeric materials, which can be operated at room temperature, has low energy consumption, is less polluting, and can firmly bond functional groups with the polymer body, into the manufacturing process of antibacterial and deodorant textile products, providing a new route for manufacturing textile products with long-lasting antibacterial and deodorant properties.

[0022] Preferably, the energy of the electron beam is between 100 keV and 10 MeV. In a preferred embodiment, the energy of the electron beam is between 500 keV and 3 MeV. It should be understood that the penetration depth of the electron beam is related to the energy, and the higher the energy, the deeper the penetration. Although less than 100 keV can generate free radicals on the surface of the textile, the penetration ability is insufficient, and the reaction usually occurs in a shallow surface layer, and the bacteria grow in the deeper layers of the textile and cannot be killed. Although the energy of more than 10 MeV has a stronger penetration ability, it exceeds the threshold of induced radioactivity production (i.e., radioactivity is also produced from the irradiated sample), and therefore cannot be used in general industrial processing. Therefore, the protection range of the present invention for the electron beam energy is between 100 keV and 10 MeV, and the preferred energy range is more suitable for textiles with a general thickness.

[0023] Preferably, the current intensity of the electron beam is between 5 mA and 2 A. In a preferred embodiment, the current intensity of the electron beam is between 50 mA and 500 mA.

[0024] Preferably, the absorbed dose is between 1 kGy and 300 kGy. In a preferred embodiment, the absorbed dose is between 5 and 60 kGy.

[0025] The long-acting, wash-resistant antibacterial and deodorizing textile product of the present invention can be obtained by the above-mentioned production method.

[0026] Preferably, the long-acting, wash-resistant antibacterial and deodorant textile product is a woven fabric, knitted fabric, nonwoven fabric, or yarn.Preferably, the textile product is a blend of various chemical fibers such as cotton, linen, silk, wool, etc. and these types of raw materials.In a preferred embodiment, the textile product is at least one of cotton, silk, wool, linen, bamboo fiber, Tencel, modal, acetate, polyester, nylon, acrylic, spandex, polyethylene, and polypropylene.It should be understood that the blending ratio of the textile product can be selected almost arbitrarily according to need, which is suitable for blended textile products because the energy of the electron beam is much higher than the covalent bond energy in the polymer structure, and can induce free radicals in almost all polymers.

[0027] Preferably, the grafting rate of the photocatalyst particles in the textile product is between 0.01% and 10%, and the grafting rate of the quaternary ammonium salt monomer in the textile product is between 0.1% and 200%. Here, the calculation formula for the grafting rate is (weight of textile product after reaction-weight of textile product before reaction) / weight of textile product before reaction×100%. In a preferred embodiment, the grafting rate of the quaternary ammonium salt monomer in the textile product is between 1% and 50%, and the total grafting rate of the photocatalyst particles in the textile product is between 0.05% and 3%. It should be understood that the grafting rate is relatively complicated, being influenced by many factors, such as whether the substrate is easy to absorb water (high or low liquid transport rate), whether the substrate is sensitive to radiation (produces more free radicals with the same dose), the compatibility between the substrate and the monomer, the type of monomer, and the monomer concentration. Because the radiation grafting technology of the present invention is suitable for the weaving of various textile products. Effect of the Invention

[0028] The method for producing a long-acting, wash-resistant antibacterial and deodorant textile product according to the present invention is to covalently bond a quaternary ammonium salt monomer and photocatalyst particles to a textile product by using an electron beam to induce a graft polymerization reaction, and the operation process can be carried out at room temperature and can be connected to the current post-processing process line of textile products.Compared with the conventional antibacterial and deodorant textile product production method in the current industry, the antibacterial and deodorant group of the antibacterial and deodorant textile product produced by the present invention is firmly bonded to the textile product and is not easily dropped off during use, the antibacterial and deodorant function lasts for a long time, and is safe for the human body and the environment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0029] The basic idea of ​​the present invention is to combine a quaternary ammonium salt with a photocatalyst and use them in textile products to complement their functions and exert a synergistic effect, with the quaternary ammonium salt exerting a rapid and wide-range bactericidal effect, suppressing odor caused by bacterial growth, and exerting the effect of adsorbing a small amount of ammonia gas, and the photocatalyst playing a role in removing odor generated from an odor source that cannot be acted on by the quaternary ammonium salt, thereby allowing the textile product to maintain a good wide-range antibacterial and deodorizing function for a long time. However, if the existing conventional technology is simply transplanted and the quaternary ammonium salt, the photocatalyst, and the textile product are combined at the same time, a synergistic effect cannot be obtained, and they will rather inhibit each other. The existing conventional technology is to attach the photocatalyst to the textile product with an adhesive, and since it relies on the adhesive, there are still disadvantages that the photocatalyst is easily dropped off and the function does not last long, and the adhesive covers a large part of the quaternary ammonium salt molecule, preventing contact with bacteria and reducing the antibacterial function of the quaternary ammonium salt.

[0030] The present invention solves the problem that in the prior art, a quaternary ammonium salt and a photocatalyst could not be fused together to produce a synergistic effect, and both the quaternary ammonium salt and the photocatalyst are firmly covalently bonded to a textile product, producing a synergistic effect between the two, thereby realizing a textile product with long-lasting broad-spectrum antibacterial and deodorizing properties; that is, by modifying the chemical structure of the photocatalyst surface, it bonds to a carbon-carbon double bond functional group that can participate in free radical addition polymerization, and is bonded to a carbon-carbon double bond-containing quaternary ammonium salt monomer by ionizing radiation, causing graft copolymerization of the photocatalyst and the quaternary ammonium salt monomer on the textile product.

[0031] The photocatalyst particles chemically modified with carbon-carbon double bonds of the present invention have multiple carbon-carbon double bonds on one particle, that is, after modification, the photocatalyst particles themselves become large crosslinking agents and are graft copolymerized with quaternary ammonium salt monomers on textile products, and the polymer graft chains formed by the polymerization of the photocatalyst and the quaternary ammonium salt monomers form a mesh structure, which is similar to sewing a button (photocatalyst particles) to a textile product with silk thread (quaternary ammonium salt graft chains), has strong bonds, does not fall off during use, and has long-lasting antibacterial and deodorizing functions.

[0032] In the present invention, there is no need to add adhesives or the like, and the surfaces of the quaternary ammonium salt monomer and the photocatalyst particles are not covered and cannot function, so the advantages of both can be combined to exert an antibacterial and deodorizing effect. Therefore, this method can impart a long-acting, wash-resistant, wide-range antibacterial and deodorizing function to textile products such as woven fabrics, knitted fabrics, and yarns, and is suitable for the manufacture of products such as T-shirts, shirts, underwear, sportswear, homewear, socks, and insoles, with excellent washability and good touch. Graft polymerization using electron beams is usually carried out at room temperature, so it is energy-saving, environmentally friendly, and low-cost. EXAMPLES

[0033] The present invention will be described in detail with reference to the preferred embodiments thereof below. In the embodiments, the experimental methods not specified in detail should be selected according to the conventional methods and conditions or the product instructions.

[0034] Example 1 At -10℃, nano TiO 2 The particles were immersed in a vinyltrichlorosilane ethanol solution (the mass percentage of vinyltrichlorosilane in the solution was 50%) for 72 hours, then filtered and dried to obtain nano-TiO with surface-modified carbon-carbon double bonds. 2 The carbon-carbon double bond-containing nano-TiO particles are obtained. 2 The particles and acryloyloxyethyltrimethylammonium chloride were ultrasonically treated in water to obtain a dispersion solution, and the nano-TiO 2 The mass percentage of the particles is 0.01%, and the mass percentage of acryloyloxyethyltrimethylammonium chloride in the dispersion solution is 50%.

[0035] The grafted cotton yarn bundle and knitted fabric are washed in cold water and then dried, and the total grafting rate of the photocatalyst particles and the quaternary ammonium salt monomer for the cotton yarn bundle and knitted fabric is measured by weighing, and the grafting rate of the photocatalyst particles is calculated by measuring the Ti element content after microwave decomposition, and the grafting rate of the quaternary ammonium salt monomer is obtained by subtracting the grafting rate of the photocatalyst particles from the total grafting rate. Through detection, the grafting rate of the quaternary ammonium salt monomer in the textile product is 50.0%, and the grafting rate of the photocatalyst particles in the textile product is 0.01%.

[0036] The antibacterial performance of the above cotton yarn bundle and knitted fabric samples is measured with reference to the American Association of Textile Chemists and Colorists AATCC 100-2012 standard, and after 20 accelerated washes (equivalent to 100 home washes) of the above cotton yarn bundle and knitted fabric samples with reference to the accelerated washing method of the AATCC 61-2003 standard, the antibacterial performance of the samples after washing is measured with reference to the reference AATCC 100-2012 standard, and the deodorizing performance of the above cotton yarn bundle and knitted fabric samples is measured with reference to the Japan Textile Evaluation Technology Council JEC 301-2013 standard.

[0037] For the results of the detection of antibacterial and deodorizing performance, please refer to Effect Example 1.

[0038] The sources of raw materials used in this example are as follows: cotton yarn bundle and knitted fabric, Shanghai Institute of Textile Science; nano-TiO 2 Particles, Vinyltrichlorosilane, Acryloyloxyethyltrimethylammonium Chloride, Sinopharm Chemical Reagent Co., Ltd.

[0039] Example 2 At 50°C, ZnO particles are immersed in vinyltrimethoxysilane aqueous solution (mass percentage of vinyltrimethoxysilane in the solution is 0.1%) for 5 minutes, then filtered and dried to obtain nano-ZnO particles with surface-modified carbon-carbon double bonds. The carbon-carbon double bond-containing nano-ZnO particles and methacryloyloxyethyl trimethylammonium chloride are ultrasonically treated in ethanol to obtain a dispersion solution, the mass percentage of nano-ZnO particles in the dispersion solution is 10%, and the percentage of methacryloyloxyethyl trimethylammonium chloride in the dispersion solution is 30%.

[0040] The silk gauze bundle and woven fabric are cut into appropriate sizes, soaked in the above dispersion solution, and then rolled once using a padder at a pressure of 0.5 kg, and then processed under an electron accelerator in a nitrogen gas atmosphere, the parameters of the electron accelerator are electron beam energy 10 MeV, electron beam current intensity 5 mA, and absorbed dose 60 kGy.

[0041] The grafted silk gauze bundle and woven fabric are washed in cold water and then dried, and the total grafting rate of the photocatalyst and the quaternary ammonium salt monomer in the textile product is measured by weighing, and the grafting rate of the photocatalyst particles is calculated by measuring the Zn element content after microwave decomposition, and the grafting rate of the quaternary ammonium salt monomer is obtained by subtracting the grafting rate of the photocatalyst particles from the total grafting rate. Through detection and calculation, the grafting rate of the photocatalyst particles in the above silk gauze bundle and woven fabric is 10%, and the grafting rate of the quaternary ammonium salt monomer is 25.5%.

[0042] The antibacterial performance of the silk gauze bundle and woven fabric samples is measured according to the American Association of Textile Chemists and Colorists AATCC 100-2012 standard, and the deodorizing performance of the silk gauze bundle and woven fabric samples is measured according to the Japan Textile Evaluation Technology Council JEC 301-2013 standard.

[0043] For the results of the detection of antibacterial and deodorizing performance, please refer to Effect Example 2.

[0044] The sources of raw materials used in this example are as follows: silk gauze bundle and woven cloth, Zhejiang Shengtai Group; nano ZnO particles, vinyltrimethoxysilane, methacryloyloxyethyltrimethylammonium chloride, Sinopharm Chemical Reagent Co., Ltd.

[0045] Example 3 At 25℃, Fe 2 O 3 The particles were immersed in a mixed aqueous solution of acryloyloxyethyltrimethoxysilane and methacryloyloxyethyltrimethoxysilane (the mass percentages of acryloyloxyethyltrimethoxysilane and methacryloyloxyethyltrimethoxysilane in the aqueous solution were 1% and 4%, respectively) for 30 minutes, and then filtered and dried to obtain nano-Fe particles with surface-modified carbon-carbon double bonds. 2 O 3 The carbon-carbon double bond-containing nano-Fe particles are obtained. 2 O 3The particles, acryloyloxyethyltrimethylammonium bromide and Tween-85 were sonicated in dimethyl sulfoxide to obtain an emulsion-like dispersion solution, and the nano-Fe in the dispersion solution was 2 O 3 The mass percentage of the particles is 0.4%, the percentage of acryloyloxyethyltrimethylammonium bromide in the dispersion solution is 0.5%, and the mass percentage of Tween-85 in the dispersion solution is 0.05%.

[0046] The polyester and spandex blended knitted fabric (the ratio of polyester and spandex is 95:5) is cut into appropriate size, immersed in the above dispersion solution, and then rolled once using a padder at a pressure of 0.2 kg, and then processed under an electron accelerator in a nitrogen gas atmosphere, the parameters of the electron accelerator are electron beam energy 3 MeV, electron beam current intensity 10 mA, and the absorbed dose is 300 kGy.

[0047] The grafted polyester and spandex blended knitted fabric was washed in cold water and then dried. Measurement and calculation were performed by weighing method and element content analysis method. The grafting rate of the photocatalyst particles in the polyester and spandex blended knitted fabric was 0.05%, and the grafting rate of the quaternary ammonium salt monomer was 0.1%.

[0048] Through the above steps, a polyester / spandex blended knitted fabric having antibacterial and deodorizing properties is produced.

[0049] The sources of raw materials used in this example are as follows: polyester and spandex blended knitted fabric, Zhejiang Shengtai Group; nano ZnO particles, acryloyloxyethyl trimethoxysilane, methacryloyloxyethyl trimethoxysilane, acryloyloxyethyl trimethyl ammonium bromide, Sinopharm Chemical Reagent Co., Ltd.

[0050] Example 4 At 5℃, nano-TiO2 and SnO 2 Mixture of nano-TiO particles 2 and SnO 2 The nano-Fe particles (mass percentage of the Fe nanoparticles is 100:1) were immersed in a methacryloyloxypropyltrimethoxysilane aqueous solution (mass percentage of the methacryloyloxypropyltrimethoxysilane in the solution is 20%) for 30 minutes, and then filtered and dried to obtain nano-Fe particles having surface-modified carbon-carbon double bonds. 2 O 3 The carbon-carbon double bond-containing nano-TiO particles are obtained. 2 and SnO 2 The particles, methacryloyloxypropyltrimethylammonium chloride, were ultrasonically treated in water to obtain a dispersion solution, and the nano-TiO 2 and SnO 2 The total mass percentage of the particles is 3% and the percentage of methacryloyloxypropyltrimethoxysilane in the dispersion solution is 38%.

[0051] The hemp, wool and polypropylene blended fabric (hemp, wool and polypropylene ratio is 88:10:2) is cut into appropriate size, immersed in the above dispersion solution, and then rolled once with a padder at a pressure of 1 kg, and then processed under an electron accelerator in a vacuum atmosphere, the parameters of the electron accelerator are electron beam energy 2 MeV, electron beam current intensity 50 mA, and absorbed dose is 5 kGy.

[0052] The grafted hemp, wool and polypropylene blended woven fabric was washed in cold water and then dried. Measurement and calculation were performed by weighing method and element content analysis method. The graft rate of the photocatalyst particles in the hemp, wool and polypropylene blended woven fabric was 3%, and the graft rate of the quaternary ammonium salt monomer was 200%.

[0053] Through the above steps, an antibacterial and deodorizing blended woven fabric of hemp, wool and polypropylene is produced.

[0054] The sources of raw materials used in this example are as follows: hemp, wool and polypropylene blended fabric, Zhejiang Shengtai Group; nano TiO 2 , nano SnO 2 , Methacryloyloxypropyltrimethoxysilane, Methacryloyloxypropyltrimethylammonium chloride, Sinopharm Chemical Reagent Co., Ltd.

[0055] Example 5 At 40℃, SrTiO 3 The particles were immersed in a mixed aqueous solution of vinyltris(β-methoxyethoxy)silane and vinyltri-t-butoxysilane (the mass percentages of vinyltris(β-methoxyethoxy)silane and vinyltri-t-butoxysilane in the aqueous solution were 20% and 10%, respectively) for 48 hours, and then filtered and dried to obtain nano-SrTiO with surface-modified carbon-carbon double bonds. 3 The carbon-carbon double bond-containing nano-SrTiO particles are obtained. 3 The particles, methacryloyloxyethyltrimethylammonium bromide, and dimethyldiallylammonium chloride were ultrasonically treated in water to obtain a dispersion solution, and the nano-SrTiO 3 The mass percentage of the particles is 5%, the percentage of methacryloyloxyethyltrimethylammonium bromide in the dispersion solution is 15%, and the mass percentage of dimethyldiallylammonium chloride in the dispersion solution is 35%.

[0056] The cotton, modal and ethylene blended woven fabric (cotton, modal and ethylene ratio is 80:15:5) is cut into appropriate size, immersed in the above dispersion solution, rolled once with a padder at a pressure of 0.2 kg, and then placed under an electron accelerator in a nitrogen gas atmosphere for processing, the parameters of the electron accelerator are electron beam energy 500 keV, electron beam current intensity 500 mA, and the absorbed dose is 30 kGy.

[0057] The grafted cotton, modal and ethylene blended woven fabric was washed in cold water and then dried. Measurement and calculation were performed by weighing method and element content analysis method. The grafting rate of the photocatalyst particles in the cotton, modal and ethylene blended woven fabric was 4.5%, and the total grafting rate of the quaternary ammonium salt monomer was 50.0%.

[0058] Through the above steps, a blended woven fabric of cotton, modal and ethylene with antibacterial and deodorant properties is produced.

[0059] The sources of raw materials used in this example are as follows: Cotton, Modal and Ethylene Blend Fabric, Zhejiang Shengtai Group; Nano SrTiO 3 Particles, Vinyltris(β-methoxyethoxy)silane, Vinyltri-t-butoxysilane, Methacryloyloxyethyltrimethoxysilane, Methacryloyloxyethyltrimethylammonium bromide, Dimethyldiallylammonium chloride, Sinopharm Chemical Reagent Co., Ltd.

[0060] Example 6 At 15℃, nano WO 3 and SiO 2 Mixture with nanoparticles (nanoWO 3 and SiO 2 The nano-WO particles having a surface-modified carbon-carbon double bond were immersed in a mixed ethanol solution of vinyltri-t-butylperoxysilane, vinyltriacetoxysilane, and acryloyloxyethyltrimethoxysilane (the mass percentages of vinyltri-t-butylperoxysilane, vinyltriacetoxysilane, and acryloyloxyethyltrimethoxysilane in the aqueous solution were 1%, 5%, and 20%, respectively) for 24 hours, and then filtered and dried to obtain nano-WO particles having a surface-modified carbon-carbon double bond. 3 and SiO 2 The carbon-carbon double bond-containing nano-SrTiO particles are obtained. 3The particles, (3-acrylamidopropyl)trimethylammonium chloride, and (3-acrylamidopropyl)trimethylammonium bromide were ultrasonically treated in water to obtain a dispersion solution, and nano-WO in the dispersion solution was 3 and SiO 2 The total mass percentage of the particles is 0.5%, the percentage of (3-acrylamidopropyl)trimethylammonium chloride in the dispersion solution is 0.5%, and the mass percentage of (3-acrylamidopropyl)trimethylammonium bromide in the dispersion solution is 5%.

[0061] The nylon and acetate blended woven fabric (the ratio of nylon to acetate is 60:40) is cut to an appropriate size, immersed in the above dispersion solution, and then rolled once using a padder at a pressure of 2 kg, and then processed under an electron accelerator in a nitrogen gas atmosphere, the parameters of which are electron beam energy 500 keV, electron beam current intensity 100 mA, and absorbed dose 80 kGy.

[0062] The grafted nylon and acetate blended woven fabric was washed in cold water and then dried. Measurements and calculations were made by weighing and element content analysis. The graft rate of the photocatalyst particles in the nylon and acetate blended woven fabric was 0.5%, and the graft rate of the quaternary ammonium salt monomer was 1%.

[0063] Through the above steps, a nylon and acetate blended woven fabric with antibacterial and deodorizing properties is produced.

[0064] The sources of raw materials used in this example are as follows: Nylon and acetate blended woven fabric, Zhejiang Shengtai Group; Nano WO 3 , nano SiO 2, Vinyltrit-butylperoxysilane, Vinyltriacetoxysilane, Acryloyloxyethyltrimethoxysilane, (3-acrylamidopropyl)trimethylammonium chloride, (3-acrylamidopropyl)trimethylammonium bromide, Sinopharm Chemical Reagent Co., Ltd.

[0065] Example 7 Nano-TiO in methacryloyloxypropyltrimethoxysilane at 20°C 2 (the mass percentage of methacryloyloxypropyltrimethoxysilane in the aqueous solution is 20%) for 48 hours, and then filtered and dried to obtain nano-TiO having surface-modified carbon-carbon double bonds. 2 The carbon-carbon double bond-containing nano-TiO particles are obtained. 2 The particles, methacryloyloxyethyltrimethylammonium bromide, dimethyldiallylammonium chloride, and dimethyldiallylammonium bromide were ultrasonically treated in water to obtain a dispersion solution, and the nano-TiO in the dispersion solution was 2 The mass percentage of the particles was 0.1%, and the mass percentages of methacryloyloxyethyltrimethylammonium bromide, dimethyldiallylammonium chloride, and dimethyldiallylammonium bromide in the dispersion solution were 0.1%, 1%, and 10%, respectively.

[0066] The bamboo fiber and Tencel blended knitted fabric (bamboo fiber and Tencel ratio is 80:20) is cut into appropriate size, immersed in the above dispersion solution, and then rolled once using a padder at a pressure of 2 kg, and then processed under an electron accelerator in a nitrogen gas atmosphere, the parameters of the electron accelerator are electron beam energy 100 keV, electron beam current intensity 20 mA, and absorbed dose 40 kGy. The grafted bamboo fiber and Tencel blended knitted fabric was washed in cold water and then dried, and measured and calculated by weighing method and element content analysis method. The graft rate of photocatalyst particles in the bamboo fiber and Tencel blended knitted fabric was 0.1%, and the graft rate of quaternary ammonium salt monomer was 10.0%.

[0067] Through the above steps, a blended knitted fabric of bamboo fiber and Tencel with antibacterial and deodorizing properties is produced.

[0068] The sources of raw materials used in this example are as follows: bamboo fiber and Tencel blended knitted fabric, Zhejiang Shengtai Group; nano TiO2, methacryloyloxypropyltrimethoxysilane, vinyltriacetoxysilane, acryloyloxyethyltrimethoxysilane, methacryloyloxyethyltrimethylammonium bromide, dimethyldiallylammonium chloride, dimethyldiallylammonium bromide, Sinopharm Chemical Reagent Co., Ltd.

[0069] Example 8 At 40℃, nano WO 3 and SiO 2 and SnO 2 Mixture with nanoparticles (nanoWO 3 and SiO 2 and SnO 2 The nano-WO having surface-modified carbon-carbon double bonds was obtained by immersing the nano-WO having surface-modified carbon-carbon double bonds in an aqueous solution of acryloyloxyethyltrimethoxysilane (the mass percentage of acryloyloxyethyltrimethoxysilane in the aqueous solution is 1%) for 72 hours, and then filtering and drying the nano-WO having surface-modified carbon-carbon double bonds. 3 and SiO 2 and SnO 2 A mixture of the carbon-carbon double bond-containing nano WO particles is obtained. 3 and SiO 2 and SnO 2The mixture of the particles, acryloyloxyethyl trimethyl ammonium chloride, and methacryloyloxyethyl trimethyl ammonium chloride was ultrasonically treated in water to obtain a dispersion solution, and the nano WO 3 and SiO 2 and SnO 2 The total mass percentage of the mixture with the particles was 5%, and the mass percentages of acryloyloxyethyltrimethylammonium chloride and methacryloyloxyethyltrimethylammonium chloride in the dispersion solution were 10% and 0.1%, respectively.

[0070] The polyethylene nonwoven fabric is cut to an appropriate size, soaked in the above dispersion solution, and then rolled once using a padder at a pressure of 2 kg, and then placed under an electron accelerator in a nitrogen gas atmosphere for processing, the parameters of the electron accelerator are electron beam energy 1.5 MeV, electron beam current intensity 15 mA, and absorbed dose 250 kGy.

[0071] The grafted polyethylene nonwoven fabric was washed in cold water and then dried. Measurements and calculations were made by weighing and element content analysis. The grafting rate of the photocatalyst particles in the blended knitted fabric of cotton, polyester and spandex was 3.0%, and the total grafting rate of the quaternary ammonium salt monomer was 14.7%.

[0072] Through the above steps, an antibacterial and deodorizing polyethylene nonwoven fabric is produced.

[0073] The sources of raw materials used in this example are as follows: polyethylene nonwoven fabric, Zhejiang Shengtai Group; Nano WO 3 , nano SiO 2 , nano SnO 2 , Acryloyloxyethyltrimethoxysilane, Acryloyloxyethyltrimethylammonium chloride, Methacryloyloxyethyltrimethylammonium chloride, Sinopharm Chemical Reagent Co., Ltd.

[0074] Effect Example 1 Table 1. Antibacterial performance test results of the cotton yarn bundle and knitted fabric samples produced in Example 1

[0075] [Table 1]

[0076] The antibacterial performance of the long-acting, wash-resistant antibacterial and deodorizing cotton yarn bundle and knitted fabric samples produced in Example 1 above was tested in accordance with the AATCC 100-2012 standard, and the results are shown in Table 1. The bacterial species selected in the antibacterial test, Escherichia coli, is a representative species of Gram-negative bacteria, Staphylococcus aureus is a representative species of Gram-positive bacteria, and Candida albicans is a representative species of fungi. As can be seen from Table 1, the antibacterial rates of the three bacterial species for the cotton yarn bundle and knitted fabric samples produced in the example were all 99%, demonstrating excellent antibacterial performance. Furthermore, after 20 accelerated washing cycles (equivalent to 100 home washes), the antibacterial rate remained almost unchanged, still exceeding 99%.

[0077] Table 2. Deodorizing performance test results of the cotton yarn bundle and knitted fabric samples produced in Example 1

[0078] [Table 2]

[0079] With reference to JEC 301-2013, the deodorizing performance of the cotton yarn bundle and knitted fabric samples with long-acting wash-resistant antibacterial and deodorizing properties produced in Example 1 was tested, with the results shown in Table 2. The removal rate of the four main odors of ammonia gas, acetic acid, isovaleric acid, and nonenal of the sample produced in Example 1 exceeded the JEC standard requirement (70% or more), and the odor removal rate remained good after 10 washes in accordance with the JEC standard.

[0080] The above antibacterial and deodorizing test results show that the method of the present invention can firmly bind antibacterial groups to textile products, thereby allowing the antibacterial performance of the textile products to last for a very long time.

[0081] Effect Example 2 Table 3. Antibacterial performance test results of silk gauze bundle and woven fabric samples produced in Example 2

[0082] [Table 3]

[0083] The antibacterial performance of the silk gauze bundle and woven fabric samples with long-acting wash-resistant antibacterial and deodorizing properties produced in Example 2 was tested in accordance with the AATCC 100-2012 standard, and the results are shown in Table 3. The bacterial species selected in the antibacterial test were Escherichia coli, a representative species of Gram-negative bacteria, Staphylococcus aureus, a representative species of Gram-positive bacteria, and Candida albicans, a representative species of fungi. As can be seen from Table 3, the antibacterial rates of the three bacterial species for the silk gauze bundle and woven fabric samples produced in Example 2 were all 99%, demonstrating excellent antibacterial performance. Furthermore, after 20 accelerated washing cycles (equivalent to 100 home washes), the antibacterial rate remained almost unchanged, still exceeding 99%.

[0084] Table 4. Results of deodorizing performance test of silk gauze bundle and woven fabric samples produced in Example 2

[0085] [Table 4]

[0086] With reference to JEC 301-2013, the deodorizing performance of the long-acting, wash-resistant, antibacterial and deodorizing silk gauze bundle and woven fabric samples prepared in Example 2 was tested, with the results shown in Table 4. The removal rate of the four main odors of ammonia gas, acetic acid, isovaleric acid, and nonenal of the sample prepared in Example 2 exceeded the JEC standard requirement (70% or more), and after 10 washes in accordance with the JEC standard, the odor removal rate remained good with almost no decrease.

[0087] The above antibacterial and deodorizing test results show that the method of the present invention can firmly bind antibacterial groups to textile products, thereby allowing the antibacterial performance of the textile products to last for a very long time.

[0088] This is because products in the textile field are directly confronted with consumers, who have intuitive perceptions and corresponding demands regarding the color, feel, smell, color fastness, etc. of textiles. According to the manufacturing method of textile products with antibacterial and deodorant properties of the present invention, antibacterial and deodorant functions can be maintained for a long period of time without impairing the basic characteristics of clothing such as the feel of the textile products, and thus the method has practical value.

[0089] The above is only a preferred embodiment of the present invention, and does not limit the scope of the present invention. Various modifications can be made to the above embodiment of the present invention. That is, all simple and equivalent changes and modifications made based on the claims and the contents of the specification of the present invention are included in the patent protection scope of the present invention. The contents not detailed in the present invention are conventional technical contents.

Claims

1. A method for producing a long-acting, wash-resistant antibacterial and deodorizing textile product, comprising: The manufacturing method includes providing a textile product, inorganic photocatalyst particles, a carbon-carbon double bond-containing silane coupling agent, and a carbon-carbon double bond functional group-containing quaternary ammonium salt monomer, reacting the inorganic photocatalyst particles with the carbon-carbon double bond-containing silane coupling agent to modify the photocatalyst surface with carbon-carbon double bonds, inducing graft polymerization by irradiating with an electron beam, and generating active free radicals in the textile product to induce graft polymerization of the carbon-carbon double bond functional group-containing quaternary ammonium salt monomer and the photocatalyst particles modified with the carbon-carbon double bond functional group, thereby firmly fixing the polyquaternary ammonium salt and the photocatalyst particles to the textile product through covalent bonds, thereby imparting antibacterial and deodorizing functions to the textile product.

2. The inorganic photocatalyst particles are TiO 2 , ZnO, WO 3 , Fe 2 O 3 , SnO 2 , SrTiO 3 , SiO 2 At least one of a group of particles The method of claim 1 .

3. The carbon-carbon double bond-containing silane coupling agent is at least one selected from the group consisting of vinyltrichlorosilane, vinyltrimethoxysilane, vinyltriethoxysilane, vinyltris(β-methoxyethoxy)silane, vinyltri-t-butoxysilane, vinyltri-t-butylperoxysilane, vinyltriacetoxysilane, acryloyloxyethyltrimethoxysilane, acryloyloxypropyltrimethoxysilane, methacryloyloxyethyltrimethoxysilane, and methacryloyloxypropyltrimethoxysilane. The method of claim 1 .

4. The reaction between inorganic photocatalyst particles and a carbon-carbon double bond-containing silane coupling agent is characterized in that the inorganic photocatalyst particles are immersed in a water or ethanol solution of the carbon-carbon double bond-containing silane coupling agent to obtain photocatalyst particles modified with carbon-carbon double bonds. The method of claim 1 .

5. The concentration of the carbon-carbon double bond-containing silane coupling agent in water or ethanol solution is 0.1% to 50%. The method according to claim 4.

6. The reaction temperature in the reaction in which the inorganic photocatalyst particles are immersed in a water or ethanol solution of a carbon-carbon double bond-containing silane coupling agent is -10°C to 50°C, and the reaction time is 5 minutes to 72 hours. The method according to claim 4.

7. The carbon-carbon double bond functional group-containing quaternary ammonium salt monomer is at least one selected from the group consisting of acryloyloxyethyl trimethylammonium chloride, acryloyloxyethyl trimethylammonium bromide, methacryloyloxyethyl trimethylammonium chloride, methacryloyloxyethyl trimethylammonium bromide, dimethyldiallylammonium chloride, dimethyldiallylammonium bromide, (3-acrylamidopropyl) trimethylammonium chloride, and (3-acrylamidopropyl) trimethylammonium bromide. The method of claim 1 .

8. The present invention is characterized in that the fiber product, the photocatalyst particles modified with carbon-carbon double bonds, and the quaternary ammonium salt monomer containing a carbon-carbon double bond functional group are irradiated with an electron beam from an electron accelerator to induce graft polymerization. The method of claim 1 .

9. The energy of the electron beam is between 100 keV and 10 MeV. The method of claim 9.

10. The current intensity of the electron beam is characterized by being between 5 mA and 2 A. The method of claim 9.

11. The absorbed dose is between 1 kGy and 300 kGy. The method of claim 9.

12. A long-acting, wash-resistant antibacterial and deodorizing textile product, The long-acting, wash-resistant, antibacterial, deodorizing textile product is characterized in that it is obtained by the manufacturing method described in any one of claims 1 to 11.

13. The long-acting, wash-resistant antibacterial and deodorizing textile product is characterized in that it is a woven fabric, knitted fabric, nonwoven fabric, or yarn. The long-acting, wash-resistant, antibacterial and deodorizing textile product according to claim 12.

14. The graft ratio of the photocatalyst particles in the textile product is between 0.01% and 10%, and the graft ratio of the quaternary ammonium salt monomer in the textile product is between 0.1% and 200%. The long-acting, wash-resistant, antibacterial and deodorizing textile product according to claim 12.

Citation Information

Patent Citations

  • Functional nano textile and preparation method thereof

    CN103147290A

  • An antibacterial textile product and a preparing method thereof

    CN107044053A

  • Antibacterial finishing method of cotton fabrics

    CN107287899A

  • Preparation method of antibacterial finishing agent for textile fabric

    CN107881765A

  • Lasting antibacterial modified nano SiO2 dispersion

    CN108084374A